“Schizophrenia past Clozapine”: Reasons for Clozapine Discontinuation, Mortality, and Alternative Antipsychotic Prescribing - Mustafa, F. A.; Burke, J. G.; Abukmeil, S. S.; Scanlon, J. J.; Cox, M. (Pharmacopsychiatry, 2015)
Introduction: The clinical records of 190 patients with schizophrenia who discontinued clozapine between 1990 and 2012 in the county of Northamptonshire were examined, in an attempt to answer the following questions. Why do patients stop clozapine? What do physicians prescribe as an alternative? What is the mortality in this patient group?Methods: Patients’ data were extracted using their electronic records, then analysed using descriptive statistical methods.Results: Non-compliance with treatment, or with the mandatory white blood cell monitoring, was the most common reason (55.3%) for clozapine cessation, followed by neutropaenia and other adverse effects (25.2%). Death (mean age 48 years) was the third most common reason (10%), with respiratory infections accounting for more than a quarter of the deaths. 13% of the patients had died (mean age 49 years) at some point following clozapine discontinuation. In terms of the alternative antipsychotic prescribing, olanzapine was the most commonly prescribed (37.1%) drug in patients who were still under the care of the local psychiatric service (n=121), at the time of data extraction. Clozapine had been reinstated in 19% of these patients.Discussion: Our findings are generally consistent with previous studies, and they demonstrate the need for physicians to address their patients’ concerns regarding clozapine treatment, and to effectively manage any adverse effects. Sialorrhea and constipation seem to be particularly of concern, as they may be linked to clozapine– related mortality. Olanzapine was the most commonly prescribed alternative to clozapine, which suggests that it may possibly have a role in refractory schizophrenia.
Keywords: schizophrenia past clozapine; clozapine discontinuation; clozapine mortality; alternative to clozapine; olanzapine